Lexical cohesion and corpus linguistics - Flowerdew, John; Mahlberg, Michaela (Benjamins current topics, 2009)
Lexical cohesion is about meaning in text. It concerns the ways in which lexical items relate to each other and to other cohesive devices so that textual continuity is created. Traditionally, lexical cohesion (along with other types of cohesion) has been investigated in individual texts. With the advent of corpus techniques, however, there is potential to investigate lexical cohesion with reference to large corpora. This collection of papers illustrates a variety of corpus approaches to lexical cohesion. Contributions deal with lexical cohesion in relation to rhetorical structure, lexical bund.